“Se avessi un figlio!" Desideri frustrati di maternità nella poesia femminile ebraica (Altre Modernità, 2014)
The desire of maternity, mostly a frustrated desire or perceived as such, is a recurring theme in the poetry of the so-called “founding mothers” of Hebrew female poetry, namely Anda Amir-Pinkerfeld, Rachel, Esther Raab, Yocheved Bat-Miriam. Although critics have often referred to this subject as a simple expression of private grief, it plays a significant role in the process of formation of a feminine poetic discourse in Hebrew and Israeli literature. This survey reviews the contribution of this topic to Hebrew and Israeli poetry through some significant examples selected from works published from 1929 to 2009.
Keywords: poesia; produzione letteraria femminile; sterilità.